Inovasi Pembelajaran Bahasa Arab Li Aghrad Khassah Dengan Media Pembelajaran Wordwall bagi Mahasiswa Agroteknologi - Fatayati, Umma; Rahmawati, Fitra Awalia; Fauziah, Rahmah; Assyari, Achmed Zidane (PT. Student RIhlah Indonesia, 2025)
This study aims to explore the innovation of using the Wordwall application as a learning medium for Arabic language instruction—specifically tailored to the needs of students in the Agrotechnology study program at Darussalam Gontor University. Adopting a qualitative approach through a case study method, the research seeks to illustrate how Wordwall is implemented in the Arabic language learning process for specific purposes (Li Aghrad Khassah) and assess its overall effectiveness. Data collection methods included interviews, observations, and documentation. The data were analyzed using the Miles and Huberman model. Findings indicate that integrating Wordwall into Arabic language learning significantly supports students’ comprehension, particularly regarding content relevant to Agrotechnology. This improvement is evidenced by the comparison between pre-test and post-test scores—students in classes A and C scored 42% on the pre-test, which increased to 86% on the post-test, showing a notable enhancement in their understanding. Despite its benefits, the use of this application also faces certain challenges, primarily due to the reliance on a stable internet connection.